2006
DOI: 10.1007/s00441-006-0256-7
|View full text |Cite
|
Sign up to set email alerts
|

Block of mitochondrial apoptotic pathways in lizard ovarian follicle cells as an adaptation to their nurse function

Abstract: Pyriforms are ovarian follicle nurse cells that undergo apoptosis at the end of previtellogenesis and are completely eliminated by the epithelium. This event is accompanied by the active transfer of organelles and macromolecules to the oocyte via an intercellular bridge. Since it would be a nonsense for damaged mitochondria to reach the oocyte, we have postulated that pyriform cells have adapted their apoptotic machinery to prevent mitochondrial degradation. To verify this hypothesis, we have studied mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…As expected, ROS accumulation in ovarian cells and whole tissues reached high levels, while MDA and T-AOC levels were increased and decreased, respectively, suggesting a serious OS and potential mitochondrial dysfunction in ovarian cells of ZP3-immunized mice, and the resulting side effects maybe also associated with the inflammation in the AOD model (11,18,19). Moreover, there are conclusive evidence has demonstrated that mitochondrial OS is a key activator of apoptosis-induced follicles depletion (47)(48)(49)(50). Therefore, evaluation of caspase, antiapoptotic and pro-apoptotic protein levels was further examined and it appeared that mitochondrial apoptotic pathway was involved in the progression of AOD, with apoptosis-induced follicular damage found to directly cause ovarian inflammationassociated reduction of follicle number.…”
Section: Discussionsupporting
confidence: 60%
“…As expected, ROS accumulation in ovarian cells and whole tissues reached high levels, while MDA and T-AOC levels were increased and decreased, respectively, suggesting a serious OS and potential mitochondrial dysfunction in ovarian cells of ZP3-immunized mice, and the resulting side effects maybe also associated with the inflammation in the AOD model (11,18,19). Moreover, there are conclusive evidence has demonstrated that mitochondrial OS is a key activator of apoptosis-induced follicles depletion (47)(48)(49)(50). Therefore, evaluation of caspase, antiapoptotic and pro-apoptotic protein levels was further examined and it appeared that mitochondrial apoptotic pathway was involved in the progression of AOD, with apoptosis-induced follicular damage found to directly cause ovarian inflammationassociated reduction of follicle number.…”
Section: Discussionsupporting
confidence: 60%
“…α spectrine is required for germ line cell division and differentiation in the Drosophila ovary. Notothenoids have an unusual abundance of spectrine suggesting that the various isoforms present may carry out different functions during oocyte maduration (Tammaro et al, 2007) Pax5 encodes a member of the paired box family of transcription factors. This gene encodes the B-cell lineage specific activator protein and also its expression has been detected in developing central nervous system and testis and so may play a role in neural development and spermatogenesis (Adams et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis would end with the formation of a few apoptotic bodies that would be phagocytosed by the small cells (Motta et al 1996) or, alternatively, transferred into the oocyte and packed with the yolk as suggested by the presence of internucleosomal DNA in yolk globlets . The existence of an alternative apoptosis route in LP pyriforms is supported by evidence that, in these cells, the mitochondrial pathway is also physiologically inhibited, as LP pyriforms over-express the mitochondrial anti-apoptotic factor bcl-2 (Tammaro et al 2007). …”
Section: Discussionmentioning
confidence: 94%